Knowledge production on sport economics: a systematic review - Nadson Santana Reis; Vitor Húngaro; Ywry Crystiano da Silva Magalhâes; Fernando Mascarenhas (Revista da Educação Física)
The study analyzes the scientific production that deals with the economic activity of the sport. This is a systematic review that evaluates scientific papers published in the last Olympic cycle (2012-2016) in national and international journals, in English, Spanish and Portuguese, indexed to the Portal of Journals of Capes (Coordination for the Improvement of Higher Education Personnel). From the content analysis, 355 studies were examined that, despite their diversity, were grouped into 16 categories. The considerations suggest an ample process of commercialization of the sport as a cultural commodity and, also, vehicle of sale and propagation of other products.